Endoscopic management of gastrointestinal motility disorders – part 1: European Society of Gastrointestinal Endoscopy (ESGE) Guideline - Weusten, Bas L. A. M.; Barret, Maximilien; Bredenoord, Albert J.; Familiari, Pietro; Gonzalez, Jan-Michel; van Hooft, Jeanin E.; Ishaq, Sauid; Lorenzo-Zúñiga, Vicente; Louis, Hubert; van Meer, Suzanne; Neumann, Helmut; Pohl, Daniel; et al. (Endoscopy, 2020)
Main Recommendations ESGE recommends the use of a graded pneumatic dilation protocol in achalasia, starting with a 30-mm dilation and followed by a 35-mm dilation at a planned interval of 2 – 4 weeks, with a subsequent 40-mm dilation when there is insufficient relief, over both a single balloon dilation procedure or the use of a larger balloon from the outset. Strong recommendation, high quality of evidence, level of agreement 100 %. ESGE recommends being cautious in treating spastic motility disorders other than achalasia with peroral endoscopic myotomy (POEM). Strong recommendation, very low quality of evidence, level of agreement 87.5 %. ESGE recommends against the routine use of botulinum toxin injections to treat patients with non-achalasia hypercontractile esophageal motility disorders (Jackhammer esophagus, distal esophageal spasm). However, if, in individual patients, endoscopic injection of botulinum toxin is chosen, ESGE recommends performing injections into four quadrants of the lower esophageal sphincter and in the lower third of the esophagus. Strong recommendation, low quality of evidence, level of agreement 78.6 %. ESGE recommends that endoscopic pylorus-directed therapy should be considered only in patients with symptoms suggestive of gastroparesis in combination with objective proof of delayed gastric emptying using a validated test, and only when medical therapy has failed. Strong recommendation, very low quality of evidence, level of agreement 100 %. ESGE recommends against the use of botulinum toxin injection in the treatment of unselected patients with gastroparesis. Strong recommendation, high quality of evidence, level of agreement 92.9 %. ESGE recommends consideration of gastric peroral endoscopic myotomy (G-POEM) in carefully selected patients only, because it is an emerging procedure with limited data on effectiveness, safety, and durability. G-POEM should be performed in expert centers only, preferably in the context of a clinical trial. Strong recommendation, low quality of evidence, level of agreement 100 %.